A cost-effective and miniaturized SPN deployment strategy for group customer dedicated lines - Cheng CHEN; Han WANG; Shuchong NAN (Dianxin kexue)
With the change of networking mode in the evolution of 5G network, SPN is faced with the limitations of ubiquitous coverage, which leads to the long access distance of the passenger dedicated line customers.Based on the operator's benefit-oriented construction idea, in order to solve the network benefit problem in the process of further deepening SPN coverage.Three sink deployment strategies were proposed for different scenarios, taking the empirical value cost of typical configurations as an example.By building a simulation environment, Gaussian mixture model was used to simulate the distribution characteristics of group customers, and the relationship between the total number of customers, the number of sinking SPN devices and customer coverage in sparse, common and dense scenarios were analyzed, and the network benefits of different sinking strategies were tested.The simulation results show that strategy 3 only faces the area coverage with high sinking efficiency when the total number of customers is 600, and the maximum coverage rate can only reach 55.27%.However, with the increase of customer points, the maximum coverage rate of strategy 3 can reach 82.71%, which has obvious coverage advantages.At the same time, the average number of sunk equipment can cover the highest number of customers, realizing the high coverage ability under the condition of ensuring high efficiency.